Using Social Science to Improve Outreach to Protect Endangered Aquatic Animals: The Case of Freshwater Mussels in Indiana. (2nd September 2019) - Bentlage, Belyna M.; Esman, Laura A.; Fisher, Brant; Prokopy, Linda S.
Abstract: Freshwater mussel populations in North America have been declining over the past two centuries due to a variety of land‐use changes and anthropogenic water quality degradation. The Tippecanoe River, located in northcentral Indiana, was once home to the world's largest population of clubshell mussels. Currently, the river supports six federally listed species. The Indiana Department of Natural Resources (IDNR) partnered with Purdue University to design and implement an outreach and education campaign to raise awareness about and promote protection of these imperiled species. This article details how researchers used the principles of community‐based social marketing to create and evaluate the campaign. Lessons learned and recommendations for future campaigns are provided.